2017
DOI: 10.1186/s13063-017-2360-2
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality of randomized controlled trials in patients with HIV on antiretroviral therapy: a systematic review

Abstract: BackgroundTo allow for correct evaluation of clinical trial results, readers require comprehensive, clear, and highly transparent information on the methodology used and the results obtained. This study aimed to evaluate the quality of reporting in articles on randomized controlled trials (RCTs) of antiretroviral therapy (ART) in the field of HIV/AIDS.MethodsWe searched for original articles on RCTs of ART developed in the field of HIV/AIDS in PubMed database by 5 April 2016. Searched articles were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Research generally suggests inadequately-performed blinding in the RCTs conducted in Iran and other countries. 15,33,35 Low RoB was assigned to attrition bias in 56.3% of cases, suggesting a small number of patients failing to follow up in the Iranian RCTs. In line with studies assessing Iranian RCTs in this domain, the present study found that Iranian researchers are relatively successful in providing data on the patients withdrawing from the study.…”
Section: Discussionmentioning
confidence: 99%
“…Research generally suggests inadequately-performed blinding in the RCTs conducted in Iran and other countries. 15,33,35 Low RoB was assigned to attrition bias in 56.3% of cases, suggesting a small number of patients failing to follow up in the Iranian RCTs. In line with studies assessing Iranian RCTs in this domain, the present study found that Iranian researchers are relatively successful in providing data on the patients withdrawing from the study.…”
Section: Discussionmentioning
confidence: 99%
“…One-third of the studies were also evaluated as low-risk in terms of detection bias, which can be explained by the unwillingness of Iranians to participate in completely-blinded trials and failure to report the study details, which made it di cult for the reviewers to assess bias. Research generally suggests inadequately-performed blinding in the RCTs conducted in Iran and other countries [15,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies which evaluated Iranian or RCTs from other countries have also pointed out that blinding is usually not adequately performed. 15, 28, 29…”
Section: Discussionmentioning
confidence: 99%